Preparation of plasmid DNA by sequential enzymatic digestion - Hyman, E D (BioTechniques, 1992)
A new method for the preparation of plasmid DNA from Escherichia coli, sequential enzymatic digestion, is described. The method is based on sequential and selective enzymatic digestion of all components of E. coli except for the supercoiled plasmid DNA. The key enzymes are exonuclease I and exonuclease III that specifically hydrolyze linear chromosomal DNA and are unable to attack supercoiled plasmid DNA under controlled conditions. Isolated plasmid DNA can be sequenced and digested with restriction enzymes